Methyl Bromide Fumigant REDs Regulations Overview - Andrew W. MacRae; Joseph Noling (EDIS)
HS1166, a 10-page fact sheet by Andrew W. MacRae and Joseph Noling, provides growers, applicators, and owner/operators with an overview of new mitigation measures and reporting requirements for methyl bromide. Published by the UF Department of Horticultural Sciences, April 2010.